2006
DOI: 10.1007/s00520-006-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Review of patterns of practice and patients’ preferences in the treatment of bone metastases with palliative radiotherapy

Abstract: Despite strong evidence supporting the use of single fraction RT, current practices and preferences favor multiple fractions for the treatment of bone metastases. This has significant implications for the overall quality of life, RT department workload, costs to healthcare systems, and patient convenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…The fee-for-service payment model, which is more common in the United States relative to abroad and tends to incentivize overutilization, therefore seems to be a primary driver of fractionation trends in the United States (37). A relationship between fee-for-serviceebased payment and increased use of fractionated treatment has been demonstrated, consistent with this assertion (29,37,38).…”
Section: Percentage Receiving Selected Fractionationmentioning
confidence: 58%
See 1 more Smart Citation
“…The fee-for-service payment model, which is more common in the United States relative to abroad and tends to incentivize overutilization, therefore seems to be a primary driver of fractionation trends in the United States (37). A relationship between fee-for-serviceebased payment and increased use of fractionated treatment has been demonstrated, consistent with this assertion (29,37,38).…”
Section: Percentage Receiving Selected Fractionationmentioning
confidence: 58%
“…Nonetheless, maintenance of or improvement in quality of life, receipt of effective treatment, convenience, and minimization of time spent in the medical setting are endpoints known to be of value to patients with terminal malignancies (14,21,29,30). We observed that the distance from a patient's home to the treating facility was the strongest independent predictor of SF-RT receipt, which is indicative of the importance placed on convenience by patients.…”
Section: Discussionmentioning
confidence: 73%
“…The reasons proposed for this reticence have included regional variation in participation in related RCTs, a lack of experience with large fraction sizes, and the influence of reimbursement (41,42). Factors other than published data have been reported to strongly influence prescription patterns, including patient, tumor, and institutional factors, and physician attitudes (46).…”
Section: Introductionmentioning
confidence: 98%
“…Studies conducted in the United States suggest that the use of single-fraction radiotherapy ranges from 3% to 14% 24 . Despite the evidence for single-fraction radiation for palliation of uncomplicated bone metastases, several survey-based studies suggest that single-fraction regimens are underused internationally 21,[25][26][27][28] . A 2009 practice patterns survey found that 20 Gy delivered in 5 fractions was the schedule most commonly prescribed by Canadian radiation oncologists 21 .…”
Section: Discussionmentioning
confidence: 99%